Indikator Degradasi Ekosistem Perairan: Fenomena Ledakan Populasi Ikan Sapu-Sapu - Ummi Maulinda Sari; Najwa Khairunnisa; Nazwa Keysa Ningrum; Asyifa Salsabila; Jesika Maretta Br Manullang; M. Alpharabie Zulwin Putra; Muhammad Hujjatul Isdihar; Ilyas Rahman; Muhammad Akiel Andwika Ettaqi; Kaka Noeca Pratama; Zullia Adhia Ayzila; Yen Norahma Yeni (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Indonesia’s aquatic ecosystems play an important role in maintaining biodiversity and supporting community livelihoods. However, human activities such as waste disposal have reduced the quality of aquatic environments and triggered the emergence of invasive species, one of which is the suckermouth catfish (Pterygoplichthys). This study aims to analyze the population explosion of suckermouth catfish as an indicator of aquatic ecosystem degradation. The research employed a Systematic Literature Review (SLR) method using secondary data obtained from national and international journal articles accessed through Google Scholar, ScienceDirect, and the Garuda portal. Articles were selected based on predetermined inclusion and exclusion criteria. The results of the review indicate that suckermouth catfish have spread widely and dominate populations in several Indonesian aquatic regions. The population explosion is influenced by environmental pollution, high adaptability, the absence of natural predators, and human activities. The impacts include a decline in local fish biodiversity, disruption of food chains, and habitat degradation. The increasing population of suckermouth catfish can therefore be used as an indicator of declining aquatic environmental quality. Consequently, population control measures, ecosystem restoration, and improved waste management are needed through collaboration between the government and the community.